Mode-Locked and Tunable 3.5 μm Fiber Laser Using an Acousto-Optic Modulator - Henderson-Sapir, Ori; Bawden, Nathaniel; Theodosiou, Antreas; Majewski, Matthew R.; Kalli, Kyriacos; Jackson, Stuart D.; Ottaway, David J. (My University, 2023)
A mode-locked, dual-wavelength pumped 3.5 μm fiber laser using frequency shifted feedback utilizing an acousto-optic modulator is reported. Pulses of 3.8 ps with 9.7 nJ were obtained at a repetition rate of 37.75 MHz. The resulting peak power is 2.55 kW. An electronically wavelength swept, mid-IR interrogator is built to characterize a mid-IR fiber Bragg grating.
Keywords: Acoustooptic modulation; dual-wavelength pumping; erbium; FBG interrogator; frequency shifted feedback; lasers; mid-infrared; mode locked lasers; optical fiber lasers; ZBLAN